Isolation of resistance gene candidates (RGCs) and characterization of an RGC cluster in cassava - López, C.E.; Zuluaga, A.P.; Cooke, R.D.; Delseny, M; Tohme, Joseph M.; Verdier, Valerie M. (Springer, 2003)
Plant disease resistance genes (R genes) show significant similarity amongst themselves in terms of both their DNA sequences and structural motifs present in their protein products. Oligonucleotide primers designed from NBS (Nucleotide Binding Site) domains encoded by several R-genes have been used to amplify NBS sequences from the genomic DNA of various plant species, which have been called Resistance Gene Analogues (RGAs) or Resistance Gene Candidates (RGCs). Using specific primers from the NBS and TIR (Toll/Interleukin-1 Receptor) regions, we identified twelve classes of RGCs in cassava ( Manihot esculenta Crantz). Two classes were obtained from the PCR-amplification of the TIR domain. The other 10 classes correspond to the NBS sequences and were grouped into two subfamilies. Classes RCa1 to RCa5 are part of the first subfamily and were linked to a TIR domain in the N terminus. Classes RCa6 to RCa10 corresponded to non-TIR NBS-LRR encoding sequences. BAC library screening with the 12 RGC classes as probes allowed the identification of 42 BAC clones that were assembled into 10 contigs and 19 singletons. Members of the two TIR and non-TIR NBS-LRR subfamilies occurred together within individual BAC clones. The BAC screening and Southern hybridization analyses showed that all RGCs were single copy sequences except RCa6 that represented a large and diverse gene family. One BAC contained five NBS sequences and sequence analysis allowed the identification of two complete RGCs encoding two highly similar proteins. This BAC was located on linkage group J with three other RGC-containing BACs. At least one of these genes, RGC2, is expressed constitutively in cassava tissues.